2015
DOI: 10.5152/ucd.2015.2840
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of preoperative neutrophil lymphocyte ratio with prognosis in gastrointestinal stromal tumors

Abstract: Objective: Gastrointestinal stromal tumors are believed to play a role in immunosuppression with their local effect. In some cancers with associated inflammation, an increased pretreatment neutrophil lymphocyte ratio is considered as an indicator of poor prognosis. The aim of our study was to assess the relationship of increased blood neutrophil lymphocyte ratio with disease prognosis in patients with gastrointestinal stromal tumors. Material and Methods:The data of 78 patients who underwent surgery with the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…The results of the 5 studies were summarized in Table 9 . Among them, Perez et al 12 Atila et al, 13 Kargin et al, 15 and Goh et al 16 showed that high level of NLR was correlated with poor prognosis of GISTs. No correlation between NLR and prognosis of GISTs was found in the study reported by Racz et al 14 This may attribute to the relatively small sample size of the study.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the 5 studies were summarized in Table 9 . Among them, Perez et al 12 Atila et al, 13 Kargin et al, 15 and Goh et al 16 showed that high level of NLR was correlated with poor prognosis of GISTs. No correlation between NLR and prognosis of GISTs was found in the study reported by Racz et al 14 This may attribute to the relatively small sample size of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Çeşitli kardiyovasküler, tümöral, inflamatuar ve otoimmün hastalıklarda NLO değeri inflamasyon şiddetinin göstergesi olarak kullanılmaktadır. [19][20][21][22] NLO, inflamasyonun ucuz, kolay ve etkili bir göstergesidir. Meme, kolorektal kanserler, gastrointestinal stromal tümörler, koroner arter hastalıkları, romatoid artrit gibi hastalıklarda NLO'nun prognostik rolü çok sayıda çalışmada değerlendirilmiştir.…”
Section: Ort±ss (Min-maks) Ort±ss (Min-maks) Ort±ss (Min-maks) Punclassified
“…Correlations between the studied biomarkers and other clinicopathological features were studied and found by Feng et al, Perez et al, and Kargin et al. All of them found NLR to be correlated to mitotic count; Perez et al also found the diameter to be correlated to NLR.…”
Section: Discussionmentioning
confidence: 90%
“…As of now, five studies are available in the literature, which demonstrated an association between high NLR and reduced DFS in patients affected by GIST. Perez et al first showed that a high level of NLR was correlated with poor prognosis, followed by Kargin et al, Goh et al, Stotz et al, and Feng et al On the other hand, the sixth study on this topic by Racz et al, did not find an association between NLR and recurrence, but between PLR and DFS. PLR was associated with DFS also by Stotz et al, Goh et al, and Feng et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation